Experiences of social work intervention among mothers with perinatal mental health needs. (25th August 2019) - Lever Taylor, Billie; Mosse, Liberty; Stanley, Nicky
Abstract: Perinatal mental health difficulties are prevalent among women, and the vulnerability of young infants makes this a time when families experiencing multiple adversities may be particularly likely to attract state intervention. However, very little is known about how mothers experience social work intervention during the perinatal period. This study explored experiences of social work intervention among women with perinatal mental health difficulties. Qualitative semi‐structured interviews were carried out with 18 women with 6‐ to 9‐month‐old babies, who had been treated in England for a perinatal mental health difficulty and also had social services intervention. Interviews were analysed using thematic analysis. Findings suggested that mothers had a predominantly negative view of children's social services, especially when social workers had significant child protection concerns. The fear of being judged an unfit mother and having their babies taken away overshadowed their encounters. Mothers felt that social workers would not accept they could be good mothers in spite of their difficulties and set them up to fail. Some felt that social workers focused exclusively on the risks to the baby and did not acknowledge the mother's own needs or understand perinatal mental health. In some cases, social work intervention was described as intensifying pressure on mothers' mental health, leading to escalating difficulties and increased likelihood of care proceedings. At the same time, our study also included examples of mothers forming positive relationships with social workers, and of 'turning points' where initially negative interactions stabilised and child protection concerns lessened. Women's accounts highlighted the importance of feeling 'known' by social workers who understood and respected them. The findings also suggested there may be value in improving collaboration between social workers and mental health professionals to create more space for representation of women's needs as well as those of their babies.